2022
DOI: 10.1159/000525137
|View full text |Cite
|
Sign up to set email alerts
|

There Is a Positive Dose-Dependent Association between Low-Dose Oral Minoxidil and Its Efficacy for Androgenetic Alopecia: Findings from a Systematic Review with Meta-Regression Analyses

Abstract: <b><i>Background:</i></b> Recently, low-dose oral minoxidil (LDOM) has entered the landscape of therapies for androgenetic alopecia (AGA). We determined whether using LDOM is associated with improving AGA in a dose-dependent manner; secondarily, we examined whether a dose-dependent association also exists for safety. <b><i>Methods:</i></b> Systematic searches were conducted in PubMed and Scopus to identify studies that would be eligible for our quantitative analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The results of our study and the two previous clinical trials regarding comparing oral and topical minoxidil suggest that 1 mg oral minoxidil is at least as effective as standard topical therapy in improving AGA. However, it has been proven that there is a positive dose‐dependent relationship between low‐dose oral minoxidil and its effectiveness for AGA, while the optimum dosage of oral minoxidil for treating AGA still needs to be delineated 9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of our study and the two previous clinical trials regarding comparing oral and topical minoxidil suggest that 1 mg oral minoxidil is at least as effective as standard topical therapy in improving AGA. However, it has been proven that there is a positive dose‐dependent relationship between low‐dose oral minoxidil and its effectiveness for AGA, while the optimum dosage of oral minoxidil for treating AGA still needs to be delineated 9 …”
Section: Discussionmentioning
confidence: 99%
“…8,3,6,7,17,18 Typically, topical minoxidil causes a therapeutic response rate of 40% in male patients with AGA, while another 40% experience hair loss, and the remaining 20% report no impact on their hair. 9,23 However, recent studies suggest that oral minoxidil not only by follicular sulfotransferase but also by liver and platelet sulfotransferase might lead to higher follicular accumulation. 7 This suggests that a lower enzyme activity threshold is required for the activation of oral minoxidil compared to topical minoxidil.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the efficacy and side effects of LDOM for treating AGA appear to be dose-dependent [50, 51]. A meta-regression analysis of clinical trials found that increasing the daily dose of oral minoxidil by 1 mg in AGA patients led to an increase in total hair density of 47.1 hairs/cm 2 ( p = 0.0071) and an increase in terminal hair density of 9.1 hairs/cm 2 ( p = 0.0014), as well as a rise of 1.4 μm in hair thickness ( p = 0.013), after 24 weeks [50]. However, the study also found that a minoxidil dose increase by 1 mg may lead to a higher chance of hypertrichosis and cardiovascular side effects.…”
Section: Recommendations On Ldom Usementioning
confidence: 99%
“…However, the study also found that a minoxidil dose increase by 1 mg may lead to a higher chance of hypertrichosis and cardiovascular side effects. The risk of hypertrichosis rose by 17.6% ( p = 0.0057), and the risk of cardiovascular side effects increased by 4.8% ( p = 0.00382), after 24 weeks [50].…”
Section: Recommendations On Ldom Usementioning
confidence: 99%